PENGOLAHAN TEPUNG SAGU KERJASAMA KELOMPOK TANI HUTAN (KTH) WENDY, KPHP UNIT V SORONG SELATAN & MAHASISWA PKL KEHUTANAN UM SORONG SEBAGAI WUJUD PEMBERDAYAAN MASYARAKAT - Maruapey, Azis; Saeni, Fajrianto; Nanlohy, Lona H.; Lestaluhu, Rajab; Hahury, Sanny (Yayasan Education and Social Center, 2024)
This Community Service activity program (PkM) aims to empower the community in processing sago starch into sago flour. In this activity, the community was provided with information about processing sago starch into sago flour to increase the economic value of sago. This activity was carried out together with the Wendy Forest Farmers Group (KTH), South Sorong KPHP Unit V, UM Sorong Field Work Practice (PKL) students, where KTH was guided from selecting raw materials, processing raw materials to processing and product packaging processes. The methods used in this service activity are lectures and demonstrations with the aim of creating the community's ability to produce sago flour. The results of this activity went well with the results showing that there had been an increase in KTH's understanding and skills in carrying out the sago starch processing process, as well as community adaptation to the equipment used to support the sago starch production and processing process starting from raw material preparation, processing to packaging